Overview of Environmental Conditions from Land Use Changes in Pesisir Selatan - Aisyah Amini; Abdul Razak; Nurhasan Syah; Skunda Diliarosta (Postgraduate School, Universitas Negeri Padang, 2023)
Land use planning is the use of land for certain purposes. One issue that may arise during land planning is whether the land is appropriate or suitable for a particular purpose. For local governments, it is very important to know the income potential that exists through land use planning. One of the benefits of writing this article is to get an overview of environmental conditions and the efforts of the Pesisir Selatan Regency government in environmental management. With the increase in population, quality of life, and community welfare, land is needed to meet various needs and facilities. However, the amount of land is relatively fixed, which causes problems in land use in rural and urban areas. This study investigates the conditions of Land Use, Land Conversion, and Potential in Pesisir Selatan Regency. This research produces several conclusions, namely 1) Land in Pesisir Selatan Regency is very suitable for plantation cultivation because of its condition; and 2) Pesisir Selatan Regency has a lot of potential for mining, coastal and marine cultivation, mangroves, and coral reefs.